Penerapan Media Konkret dalam Upaya Meningkatkan Hasil Belajar Matematika Siswa Kelas 5 SD Negeri 47 Palembang - Dendi Juniansyah; Hudaida Hudaida; Helen Saputri (Journal on Education, 2024)
The low student learning outcomes in Mathematics subjects, especially in addition material, prompted research using a classroom action approach from July to August. This research involved all 30 class 5 B students at SDN 47 Palembang. The method used is classroom action research, with data obtained from student test results at the pre-cycle, cycle I and cycle II stages. The research results show an increase in Mathematics learning outcomes, especially addition material, through the application of concrete media such as the Chasm Board and the Number House. In the pre-cycle stage, the student completion rate was only 30%, then increased to 45% in cycle I, and reached 95% in cycle II. Based on the results of this research, it is recommended to use concrete media in learning Mathematics, especially in addition material.